Os fatores ambientais que influenciam na ocorrência da Leishmaniose Tegumentar Americana (LTA) no Estado do Espírito Santo - Nascimento, Geane Souza Sobral (2009)
American Tegumentary Leishmaniasis (ATL) is a parasitic disease, of chronic evolution, that affects the skin and the mucous membrane of the nose, mouth, pharynges and larynges; its etiologic agents are the protozoan of the genus Leishmania. This disease is largely disseminated around the world being influenced by geographic and climatic factors which determine the distribution of the different vectors, parasites and hosts. In Brazil, the disease occurs in all the federation states, with large variation in the incidence index among states and also between municipalities that represent them. In the Espírito Santo state (ES) the ATL presents large geographic distribution with foci in almost all municipalities in the state’s southern central region, predominating in the areas which are 50 to 750 meters above sea level. This study proposes to establish an association between environmental factors and the ATL occurrences in ES through the use of geographically referred data banks, which would be performed by means of geo processing techniques. A hundred and eighty seven (1,087) registers of patients, who were diagnosed with the disease in the ambulatory of Leishmaniasis of the Hospital Universitário Cassiano Antônio Moraes from 1978 to 2006, were used for this research. The data for analysis were represented by 2,829 localities distributed within the 78 municipalities of ES. Based on the cartographic basis of these localities a representative map of their respective areas was built. The ATL cases were geo referred over this map according to small central areas containing them using the Geographical Information System (SIG) ArcGIS version 9.2 as an operational tool. The environmental variables of temperature, topography and water supply were used to determine areas prone to ATL occurrence. The association of these three variables frames the first hierarchical level of the Natural Units of Espírito Santo (UNES) and therefore, it is available in a single map operated in SIG which was achieved from the Integrated System of Geo referred Basis of the Espírito Santo state. The over lapping of the localities’ maps with the UNES map makes it possible to classify the localities within 21 types according to the interaction of the environmental variability. Among those, 15 types were selected for the statistics analysis making it possible to determine areas categorized into two groups, which are: being one of them with and the other without the risk for the occurrence of ATL. The work shift and the tools used in this study have proved to be useful to determine riscky areas for the transmission of LTA in ES, empowering someone, furthermore, to predict the occurency of the disease in ventured areas yet not known for having registers of cases of ATL.